Transcriptome Analysis of Different Tissues Reveals Key Genes Associated With Galanthamine Biosynthesis in Lycoris longituba - Li, Qingzhu; Xu, Junxu; Yang, Liuyan; Zhou, Xiaohui; Cai, Youming; Zhang, Yongchun (Frontiers in Plant Science, 2020)
Lycoris longituba is a traditional medicinal plant containing the bioactive compound galanthamine (Gal), a type of amaryllidaceous alkaloid and can be used to treat Alzheimer’s disease. However, research on its genome or transcriptome and associated genes in the biosynthetic pathway is incomplete. In this study, we estimated the nuclear genome size of this species to be 29.47 Gb by flow cytometry. Then, RNA sequencing of the leaves, roots, and bulbs of L. longituba was carried out. After de novo assembly, 4,74,589 all-transcripts and 3,33,440 all-unigenes were finally generated. In addition, the differentially expressed genes (DEGs) were identified, and genes involved in the galanthamine metabolic pathway encoding tyrosine decarboxylase (TYDC), phenylalanine ammonia-lyase (PAL), cinnamate 4-hydroxylase (C4H), p-coumarate 3-hydroxylase (C3H), norbelladine synthase (NBS), norbelladine 4'-O-methyltransferase (OMT), noroxomaritidine synthase (CYP96T1), and N-methyltransferase (NMT) were detected and validated by real-time quantitative PCR analysis. One candidate gene, Lycoris longituba O-Methyltransferase (LlOMT), was identified in the proposed galanthamine biosynthetic pathway. Sequence analysis showed that LlOMT is a class I OMT. LlOMT is localized in the cytoplasm, and biochemical analysis indicated that the recombinant LlOMT catalyzes norbelladine to generate 4′-O-methylnorbelladine. The protoplast transformation result showed that the overexpression of LlOMT could increase the Gal content. Our results indicate that LlOMT may play a role in galanthamine biosynthesis in L. longituba. This work provides a useful resource for the metabolic engineering of amaryllidaceous alkaloids.